Ag doped ZnSnO3 nanocubes: Promotion on the charge storage mechanism for supercapacitors. (October 2022) - Rani, B. Jansi; Swathi, S.; Yuvakkumar, R.; Ravi, G.; Navaneethakrishnan, P.; Al-Sehemi, Abdullah G.; Velauthapillai, Dhayalan
Abstract: Morphology optimization with noble elements doping is yet a critical, promising advance to develop an electrochemical energy storage capacity of the prepared materials for supercapacitors. With this, we have synthesized Ag element doped low-cost ZnSnO3 nanocubes via facile co-precipitation method for electrochemical energy storage application. With the compact particle size, nanoporous nature, high surface area and high adsorption properties, 20% Ag supported ZnSnO3 nanocubes outperforms than other controlled electrodes. The maximum 517 and 258 F/g capacitance was achieved from cyclic voltammogram (CV) at 10 mV/s and galvanostatic charging/discharging (GCD) profiles at 1 A/g respectively. The capacitive retention of 87.06% was achieved after 5000 cycles for the same electrode. This work will give an interesting outlook for the preparation of novel energy storage electrode materials in diverse morphology for future portable electronic devices sector. Highlights: Ag doped low-cost ZnSnO3 nanocubes via co-precipitation was developed. 20% Ag supported ZnSnO3 nanocubes outperforms than other controlled electrodes. 517 and 258 F/g was achieved from CV at 10 mV/s and GCD profiles at 1 A/g. 87.06% capacitive retention was achieved after 5000 cycles for same electrode.